Real-World Long-Term Experience on Endoxifen in Bipolar Disorder with Psychotic Symptoms - Vikas Thanvi (Case Reports in Psychiatry)
Evidence suggests that inhibition of protein kinase C (PKC) signalling may have a contributing role in the treatment of bipolar affective disorder (BPAD). Endoxifen, an active metabolite of tamoxifen, is a potent direct PKC inhibitor. This report presents a severe case of a BPAD patient with a baseline Young Mania Rating Scale (YMRS) score of 49, associated family history and addiction to psychostimulants, with no improvement by the first and second-generation antipsychotics. Treatment with endoxifen 8 mg once a day showed improvement in manic symptoms with a YMRS score of 4 and a reduction in the use of psychostimulants as well as other antipsychotic concomitant medications. No adverse effects were noted up to 8-month follow-up. Long-term treatment with endoxifen is safe and effective in severe BPAD.